2003
DOI: 10.1034/j.1600-6143.2003.00187.x
|View full text |Cite
|
Sign up to set email alerts
|

Serial Peripheral Blood Perforin and Granzyme B Gene Expression Measurements for Prediction of Acute Rejection in Kidney Graft Recipients

Abstract: In the present study we investigated whether peripheral blood gene expression measurements may serve as an early and non-invasive tool to predict renal allograft rejection. Peripheral blood was collected twice weekly after transplantation and gene expression was measured using real-time polymerase chain reaction (PCR). Recipients with acute rejection (n = 17) had higher levels of perforin and granzyme B transcript on days 5-7, 8-10, 11-13, 17-19, 20-22, and 26-29, as compared to patients without rejection (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
64
1
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(71 citation statements)
references
References 20 publications
5
64
1
1
Order By: Relevance
“…For this molecule, measuring the mRNA appeared more sensitive than measuring the protein. We additionally show for the first time that, in contrast to acute rejection where GrzB is increased in the PBMC, 16,17,26 during CAMR GrzB is significantly decreased. Furthermore, ROC analysis revealed that measuring GrzB mRNA may have potential as a decision-making tool in clinical practice to diagnose CAMR in a minimally invasive manner.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this molecule, measuring the mRNA appeared more sensitive than measuring the protein. We additionally show for the first time that, in contrast to acute rejection where GrzB is increased in the PBMC, 16,17,26 during CAMR GrzB is significantly decreased. Furthermore, ROC analysis revealed that measuring GrzB mRNA may have potential as a decision-making tool in clinical practice to diagnose CAMR in a minimally invasive manner.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, several groups have also clearly established the cytotoxic molecule granzyme B (GrzB) as a reliable intragraft, urine, and peripheral blood marker of acute kidney graft rejection. [12][13][14][15][16][17][18] Thus, although the implication of regulatory and effector responses has been addressed for AR, so far there have been no reports on the subject relative to later times posttransplant in cases of stable graft function or late renal allograft injury, such as calcineurin inhibitor (CNI) toxicity or chronic antibodymediated rejection (CAMR). Therefore, the potential involvement of FOXP3ϩ cells and any relationship to clinical and pathological correlates at later times posttransplant remain unknown.…”
mentioning
confidence: 99%
“…Granzyme mRNA expression, usually assayed by qPCR, is increasingly used as a correlate of acute rejection of allogeneic transplants, in which CTLs play a critical role. Increased granzyme mRNA levels can be detected during rejection both in the graft itself (58,59), in the blood (60,61), and even in the urine (62). Measurement of granzyme mRNA is preferable to immunostaining of granzyme proteins as a correlate of CTL activity, because the granzyme proteins do not accumulate in the cell but are rapidly and continually discharged in the lytic granules.…”
Section: Discussionmentioning
confidence: 99%
“…The cDNA was synthesized using random hexamers and oligo(dT) from 4 g of mRNA and performed with the SuperScript TM First Strand Synthesis System for RT-PCR (Invitrogen). Forward and reverse primers were designed following Guilloton et al (25) for GrB and following Simon et al (26) for PFN (Table 1). Real-time PCR was performed using an iCycler thermal cycler (Applied Biosystems 7000 Real-Time PCR System, Courtaboeuf, France) according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%